Entropic effect implication for change in polymer coils swelling state in the demixing enthalpy recovery of aqueous poly(vinyl methyl ether) solutions. Issue 3 (11th December 2018) - Song, Li; Lin, Jiaxiang; He, Yang; Li, Jingqing; Sheng, Jing; Jiang, Shichun; Huang, Dinghai
ABSTRACT: Time‐dependent demixing enthalpy recovery behavior of aqueous poly(vinyl methyl ether) (PVME) solutions exhibits distinct recovery characteristics in three concentration regions. The absence of recovery behavior below a water concentration of 38.3 wt % indicates that the PVME coil is in a globular state. The typically sigmoidal recovery behavior of demixing enthalpy above 38.3 wt % is ascribed to the reswelling of the collapsed polymer coils induced by the entropic effect. The increase in difference between the upper and lower limits indicates the continued swelling of the PVME coils. Above 65 wt %, a dominant diluting effect can be observed, and a much longer phase separation time is needed to reach the expected lower limit. In contrast, the recovery of demixing enthalpy in a wide range of water concentration (from 38.3 to 90 wt %) exhibits the same feature. The infrared spectroscopy results are in agreement with the above macroscopic differential scanning calorimetry results. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 142–151 Abstract : In lower critical solution temperature phase separation of aqueous poly(vinyl methyl ether) (PVME) solutions, the entropic effect characterized by distinct demixing enthalpy recovery behaviors, indicates the beginning of swelling of the polymer coils above 1:2 mol ratio between PVME repeating units and water. The molecular level infrared spectroscopy results are in agreement with the macroscopic differential scanning calorimetry results.